2012
DOI: 10.1007/s11764-012-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among breast cancer patients with lymphedema: a systematic review of patient-reported outcome instruments and outcomes

Abstract: Purpose Lymphedema following breast cancer surgery remains a common and feared treatment complication. Accurate information on health-related quality of life (HRQOL) outcomes among patients with lymphedema is critically needed to inform shared medical decision making and evidence-based practice in oncologic breast surgery. Our systematic review aimed to (1) identify studies describing HRQOL outcomes in breast cancer-related lymphedema (BCRL) patients, (2) assess the quality of these studies, and (3) assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
150
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 204 publications
(166 citation statements)
references
References 44 publications
9
150
0
7
Order By: Relevance
“…Latina women were found to experience poorer qol than their non-Latina counterparts 33 . Additionally, bca-related lymphedema and higher levels of fatigue were significantly associated with poorer qol 28,29 . The other factors that were associated with qol were poorer mental and physical health, poor social functioning, greater distress, and greater fear of recurrence.…”
Section: Quality Of Lifementioning
confidence: 93%
See 4 more Smart Citations
“…Latina women were found to experience poorer qol than their non-Latina counterparts 33 . Additionally, bca-related lymphedema and higher levels of fatigue were significantly associated with poorer qol 28,29 . The other factors that were associated with qol were poorer mental and physical health, poor social functioning, greater distress, and greater fear of recurrence.…”
Section: Quality Of Lifementioning
confidence: 93%
“…Of the included reviews, thirteen reported challenges faced by bca patients and survivors [27][28][29][30][31][32][33][34][35][36][37][38]40 . Their findings are categorized and described next.…”
Section: Cancer-or Cancer Treatment-related Challengesmentioning
confidence: 99%
See 3 more Smart Citations